Distance learning as a relevant educational technology in higher education institutions - S. Nestulya; S. Shara (Mukachevo State University, 2023)
The relevance of the subject is conditioned upon the fact that the current conditions, namely the COVID-19 epidemic and the introduction of martial law in Ukraine, cause dynamic changes in various spheres of human activity, including education. Despite internal and external obstacles, the educational process does not stop, and there is a need to adapt to large-scale changes in the country. The educational sector has transformed from the conventional form of the educational process, namely face-to-face, to online distance learning. Considering this, the purpose of the study is to analyse the peculiarities of implementing the distance learning process in a higher education institution in Ukraine, namely, the Higher Educational Institution of the Ukoopspilka "Poltava University of Economics and Trade". For a broad understanding of the problem and outlining the prospects for a quality educational process in the context of global processes, the study used several methods, including analysis, synthesis, deduction and surveys. The study outlines the main changes implemented by the management of higher education institutions in response to the social challenges posed by the pandemic and war. The effectiveness of using special programmes during training sessions in the distance education process is assessed. The flexibility of the educational sphere is substantiated, and the advantages and disadvantages of distance learning in terms of the quality of education are identified. The results of a student survey reflecting the real attitude of students to online learning are presented. The practical value of the work is that its results can be used by teachers to select high-quality tools designed to implement learning tasks in a distance educational format.